Hubungan Postur Kerja dengan Keluhan Gangguan Otot Rangka pada Pekerja Penyapu Jalan di Kota Manado - Wingky Rante Padang; Afnal Asrifuddin; Paul Artur Tennov Kawatu (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Musculoskeletal disorders refer to complaints felt in parts of the musculoskeletal system when muscles are subjected to prolonged repetitive static loads, which can lead to damage in joints, ligaments, and tendons. The discomfort experienced can range from mild to severe pain, potentially hindering movement and reducing work productivity. This study aims to determine the relationship between work posture and musculoskeletal complaints among street sweepers in Manado City. The research is a quantitative study using an analytical observational method with a cross-sectional design. Work posture was assessed using the Rapid Entire Body Assessment (REBA), and musculoskeletal complaints were measured using the Nordic Body Map (NBM) questionnaire. The Spearman correlation test between work posture and musculoskeletal complaints yielded a p-value of 0.660 and a correlation coefficient (r) of 0.000. The results indicate a relationship between work posture and musculoskeletal complaints among street sweepers in Manado City, with a strong correlation suggesting that the higher the posture risk score, the greater the level of complaints experienced.